DIGITALISASI UMKM MENGHADAPI TANTANGAN GLOBAL DAN PERKEMBANGAN TEKNOLOGI INFORMASI DI DESA BABAKAN LOR - Azzahra, Siti; Nurhofiani, Anisa; Pravitasari, Hikmah; Mudawanah, Siti; Wildan, M.; Ginting, Fajar Mediawan (Jurnal Abdimas Bina Bangsa, 2024)
Digitalization of MSMEs (Micro, Small and Medium Enterprises) is a strategic step in facing the challenges of globalization and the development of information technology. This digitalization process includes the use of technology to increase operational efficiency, expand market access, and increase the competitiveness of MSMEs. By utilizing digital platforms, e-commerce applications and social media, MSMEs can optimize marketing, sales and business management. However, the implementation of digitalization in MSMEs often faces obstacles such as limited resources, lack of technological skills, and problems with access to adequate digital infrastructure. This research aims to explore the factors that influence the adoption of digitalization by MSMEs in Indonesia, as well as the benefits obtained from this process. It is hoped that the results of this research can provide policy recommendations for the government and industry players to increase the success of digitalization of MSMEs, which in turn can strengthen the national economy.